Spirituality of Family in the Light of the Challenges Facing the African Family Today (Hekima Review, 2016)
The article addresses the challenges brought by the contemporary market culture that affects the African family negatively. It does so by presenting the Spirituality of Family as a spiritual paradigm which purifes, enlightens and unies the human soul with Christ. From union with Christ the family is able to build lasting relationships, marriages and families and through the family transform the whole world. The concepts of purifcation, enlightenment and unifcation with the Cosmotheandric Unity or Christ (Interior Castle) are familiar to both African religions and Christianity. The article proposes that family members, especially those who are engaged, to go through a weekend or four days seminar on these three phases of spiritual growth.